Preparation method of high-hardness transparent polyimide film
By adding modified inorganic nanoparticles to the polyamic acid resin and adopting an improved scraper coating device, the problem that the hardness and transparency of the polyimide film in the prior art is difficult to improve simultaneously, and the preparation of a high-hardness transparent film is achieved, and the production efficiency and product quality are improved.
Patent Information
- Application Number
- CN202411715713.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, when preparing transparent polyimide films, it is difficult to simultaneously improve their hardness and transparency, and the gap between the scraper and the glass substrate is high, resulting in uneven film thickness and uneven surface.
By adding modified inorganic nanoparticles to the polyamic acid resin, the hardness of the film is improved, and an improved scraper coating device, including a detection mechanism and a filling mechanism, ensure the flatness of the lower end surface of the scraper, thereby realizing the preparation of a high-hardness transparent polyimide film.
It is achieved without affecting transparency, improving the hardness of the polyimide film, reducing production costs, improving the market competitiveness of the film, and ensuring consistent thickness and flat surface of the film.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a method for preparing a high-hardness transparent polyimide film. Background Art
[0002] Polyimide resin is a heat-resistant resin, which is usually obtained by cyclization of polyamic acid synthesized by condensation reaction between aromatic tetracarboxylic anhydride and aromatic diamine. Polyimide resin exhibits excellent resistance to thermal decomposition, high resistance to chemical changes (such as oxidation or hydrolysis), and excellent mechanical and electrical properties due to its molecular chain rigidity, resonance stability and strong chemical bonds. Polyimide resin has been widely used as films, coatings, molded parts and insulating materials, for example in electrical, electronic, automotive and aerospace industries. At the same time, there is an urgent need to develop a transparent, highly heat-resistant resin that has flexibility, heat resistance and mechanical strength to replace glass or ceramic materials used in display substrates such as computers and mobile phones.
[0003] The traditional preparation method is to synthesize polyamic acid from dianhydride and diamine, and prepare the film by thermal / chemical imidization dehydration. In order to improve the wear resistance and hardness of transparent polyimide film substrates, relevant personnel in the optoelectronic film industry need to apply a layer of inorganic nano-coating on both the upper and lower sides of the polyimide film substrate for double-sided hardening treatment. However, the change in thickness affects the transmittance of the transparent polyimide film, and the adhesion between the wear-resistant coating and the substrate is not very good after coating. When the conductive coating is plated or applied as a back-end touch screen, the entire conductive layer will fall off and crack, causing the touch display device to function NG, affecting the yield. Secondly, in the process of preparing the polyimide film, the polyimide resin needs to be coated with a scraper to obtain the polyimide film. In this process, the gap between the scraper and the glass substrate is required to be extremely high. Any deviation will cause the thickness of the polyimide film to become variable or the film surface to be uneven. The prior art does not have the technology to detect the condition of the lower end surface of the scraper, and it is difficult to determine whether the lower end surface is uneven or has slight defects or gaps.
[0004] Based on this, there is still room for improvement on existing technologies. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a high-hardness transparent polyimide film to solve the deficiencies in the above-mentioned prior art.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a high-hardness transparent polyimide film comprises the following steps:
[0008] Step 1: Take 50g of filler with an average particle size of 50nm, add 200g of NMP polar solvent, add 1g of KH590, mix and disperse by ultrasonic for 2h to obtain a uniform and stable modified dispersion, which is A dispersion and has a solid content of 25%;
[0009] Step 2: Take 50g of acid-treated montmorillonite powder, the specific surface area of which is 240m2 / g, add 2.5g of sodium polyamic acid powder and 200g of N,N-dimethylacetamide, mix and disperse mechanically at high speed for 2h to obtain a uniform and stable modified montmorillonite dispersion, which is dispersion B and has a solid content of 25%;
[0010] Step 3: Mix the dispersion A and the dispersion B, and continue ultrasonic dispersion for 4 hours to obtain a modified montmorillonite dispersion C;
[0011] Step 4: Add 115 g of N,N-dimethylacetamide as a solvent and 16.012 g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl as an aromatic diamine compound having a fluorine group into a flask and stir. While stirring the inside of the flask, add 22.3225 g of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl) diphthalic dianhydride as a tetracarboxylic dianhydride under a nitrogen flow for 10 minutes. In this state, adjust the temperature to a temperature range of 30° C. and continue stirring for 6 hours to perform a polymerization reaction to obtain a viscous polyamic acid solution;
[0012] Step 5: Add 8-16 g of modified montmorillonite dispersion C to the polyamic acid solution in step S4, and continue stirring for 2 h to obtain an inorganic modified polyamic acid resin;
[0013] Step 6: filtering the prepared polyamic acid resin, performing a defoaming treatment, and coating the filtered polyamic acid resin with a doctor blade coating device to obtain a polyimide gel film;
[0014] Step 7: Fix the obtained polyimide gel film on a cutting board, fix its four sides, and then gradually perform high-temperature imidization in an oven to obtain a polyimide film with a thickness of 50 um.
[0015] Preferably, the scraper coating device includes a workbench, a glass substrate is arranged in the middle of the workbench; a work frame, which is connected to the edge of the workbench through an electric slide rail; a lifting mechanism, which is installed on a cross bar arranged between the work frames, and the lower end of the lifting mechanism is connected to a detection mechanism, and the detection mechanism is slidably arranged in an inner cavity opened by the scraper; a residual mechanism, which is installed on the left side of the scraper, and a recovery mechanism used in conjunction with the residual mechanism is installed on the cross bar; a lifting and leveling mechanism, which is installed on the right side of the lower end of the workbench.
[0016] Preferably, the lifting mechanism includes a rotating part, which is connected to the threaded barrel by means of a threaded fit, and the threaded barrel is fixedly mounted in the middle of the upper end of the cross bar; a lifting part, whose upper end is horizontally rotatably connected to the rotating part, and the lifting part is slidably arranged in a sliding hole opened in the middle of the cross bar; a sliding rod, whose upper end is slidably arranged inside the lifting part, and an electric push rod is connected between the lifting part and the sliding rod; a guide rod, whose lower end is mounted on one side of the scraper, and the guide rod is slidably arranged on the cross bar.
[0017] Preferably, the detection mechanism includes a connecting plate, which is connected to the lower end of the sliding rod, and the lower end of the connecting plate is evenly installed with blocking blocks, and the lower end of the blocking block is installed with a blocking head; a movable plate, which is slidably sleeved on the blocking block up and down, and the movable plate and the connecting plate are elastically connected; a clamping piece, which is horizontally slidably arranged in a built-in groove opened at the end of the connecting plate, and the clamping piece and the built-in groove are elastically connected, and the top support piece corresponding to the position of the clamping piece is horizontally slidably arranged in the movable groove opened on the side wall of the scraper.
[0018] Preferably, fixing plates are symmetrically installed at the front and rear ends of the working frame, and a correction block is installed at the inner end of the fixing plate, and the position of the correction block corresponds to that of the top support member.
[0019] Preferably, a spray outlet is provided on the lower end surface of the scraper, and the spray outlet is composed of a rectangular groove and a spray hole connected up and down, and adjacent rectangular grooves are connected through a through hole provided at the lower end of the scraper, and a T-shaped groove is provided inside the blocking block.
[0020] Preferably, the conveying cavity opened on the left side of the scraper is connected to the rectangular groove, an input port is opened on the right side of the inner cavity, and the upper left end of the input port is connected to the closing member through a pin shaft.
[0021] Preferably, the delivery cavity comprises an output cavity, an expansion cavity, and a Z-shaped cavity, and the output cavity, the expansion cavity, and the Z-shaped cavity arranged from top to bottom are connected to each other.
[0022] Preferably, the residual mechanism includes a trigger member, which is slidably arranged in a sliding groove provided in the scraper, the middle part of the trigger member is elastically connected to the sliding groove, and the lower end of the trigger member is equipped with a partition member for controlling the flow of the Z-shaped cavity, and the middle part of the upper and middle part of the partition member is a hollow structure; a docking joint, which is fixedly installed at the upper end of the outer wall of the scraper, the output cavity is connected with the interior of the docking joint, and a partition plate is symmetrically installed on the inside of the docking joint, and a sealing plate used in conjunction with the partition plate is installed at the upper end of the spring telescopic rod, and the spring telescopic rod is fixedly installed inside the docking joint.
[0023] Preferably, the recovery mechanism includes an insertion head, which is connected to the suction port of the pump body installed on the cross bar, and the output port of the pump body is connected to the recovery frame through a hose. The recovery frame is fixed to the side end of the cross bar, and a protrusion is installed inside the insertion head.
[0024] Preferably, the lifting and leveling mechanism includes a lifting platform, which is connected to the lower end of the workbench through a lifting assembly, and the upper end surface of the lifting platform is paved with a glass layer; a liquid storage frame, which is installed below the workbench, and the liquid storage frame is connected to the docking port through a connecting pipe and a delivery pump, and the docking port is installed on the inner wall of a through groove opened at the right end of the workbench, and the through groove is located directly above the lifting platform at the initial position.
[0025] Preferably, the filler is titanium dioxide.
[0026] Preferably, the filler is zirconium dioxide.
[0027] Preferably, the filler is a mixture of titanium dioxide and zirconium dioxide.
[0028] In summary, this application includes the following beneficial technical effects:
[0029] 1. Modification of inorganic nanoparticles: using aminosilane coupling agent to make them chemically bonded with organic substances to improve their dispersibility; adding the above modified fillers to polyamic acid and thermal imidization can produce a transparent polyimide film with improved hardness;
[0030] The present invention improves the hardness of the transparent polyimide film by adding a specific inorganic filler, thereby improving the intrinsic hardness of the film material without affecting the optical performance, reducing the production cost, and improving the market competitiveness of the transparent polyimide film;
[0031] 2. In the present application, for the detection of the scraper and the gap, after the two are attached, the flatness of the lower end surface of the scraper is determined by pressing down the detection solution in the inner cavity to see if there is any seepage, and the lower end surface of the scraper is filled and leveled. At the same time, the detection solution after the detection is recovered by the residual mechanism and the recovery mechanism, and then a qualified scraper can be used for coating, so as to obtain a high-hardness transparent polyimide film with a thickness that meets the requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the structure of the present invention;
[0033] Figure 2 is a top view of the present invention;
[0034] Figure 3 The present invention Figure 2 AA section view;
[0035] Figure 4 The present invention Figure 2 BB cross-sectional view;
[0036] Figure 5 is a partial cross-sectional view of the present invention;
[0037] Figure 6 It is a cross-sectional view of the working frame, the lifting mechanism, the crossbar, the detection mechanism, the scraper, the excess mechanism, and the recovery mechanism of the present invention;
[0038] Figure 7 The present invention Figure 3 A partial schematic diagram of
[0039] Figure 8 The present invention Figure 4 A local enlarged view of point X;
[0040] Fig. 9 The present invention Figure 7 A local enlarged view of the Y position;
[0041] Fig.10 The present invention Figure 6 A local enlarged view of the Z position;
[0042] Fig.11 The present invention Figure 3 A partial enlarged view of point C;
[0043] Fig.12 The present invention Figure 5 A partial enlarged view of point D;
[0044] Fig.13 The present invention Figure 7 A partial enlarged view of point E.
[0045] Description of reference numerals: 1. workbench; 2. work frame; 3. lifting mechanism; 4. detection mechanism; 5. scraper; 6. excess mechanism; 7. recovery mechanism; 8. lifting and leveling mechanism; 11. glass substrate; 21. fixing plate; 22. correction block; 31. cross bar; 32. rotating member; 33. threaded cylinder; 34. lifting member; 35. sliding rod; 36. electric push rod; 37. guide rod; 41. connecting plate; 42. blocking block; 43. movable plate; 44. clamping member; 45. top support member; 51. rectangular groove; 52. Ejection hole; 53. Through hole; 54. Delivery chamber; 55. Input port; 56. Closing piece; 61. Trigger piece; 62. Partition piece; 63. Docking head; 64. Partition plate; 65. Sealing plate; 66. Spring telescopic rod; 71. Insertion head; 72. Pump body; 73. Recovery frame; 74. Extension piece; 81. Lifting platform; 811. Lifting assembly; 82. Glass layer; 83. Liquid storage frame; 84. Docking port; 85. Delivery pump; 531. Output chamber; 532. Expansion chamber; 533. Z-shaped chamber. DETAILED DESCRIPTION
[0046] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0047] Embodiment 1: A high-hardness transparent polyimide film, the preparation method of which is as follows:
[0048] Take 50g of titanium dioxide powder, the average particle size of which is 50nm, add 200g of NMP polar solvent, add 1g of KH590, mix and disperse ultrasonically for 2h to obtain a uniform and stable modified titanium dioxide powder dispersion. The solid content of dispersion A is 25%; take 50g of acidified montmorillonite powder, the specific surface area of which is 240m2 / g, add 2.5g of sodium polyamic acid powder and 200g of N,N-dimethylacetamide (DMAC), mix and disperse mechanically at high speed for 2h to obtain a uniform and stable modified montmorillonite dispersion. The solid content of dispersion B is 25%; mix dispersion A with dispersion B, continue ultrasonic dispersion for 4h to obtain titanium dioxide intercalation modified montmorillonite dispersion C.
[0049] In a 500 ml glass separable flask equipped with a stirring device and a stirring blade, 115 g of a solvent N,N-dimethylacetamide (DMAC) and 16.012 g (0.0500 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) as an aromatic diamine compound having a fluorine group were added and stirred to dissolve TFMB in DMAC. Next, while stirring the inside of the separable flask, 22.3225 g (0.0502 mol) of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride (6FDA) as a tetracarboxylic dianhydride was added over a period of about 10 minutes under a nitrogen gas stream, and the temperature was adjusted to a temperature range of 20 to 40° C. in this state, and the stirring was continued for 6 hours to perform a polymerization reaction, thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.005, and the concentration of the polyamic acid solution was 25% by weight.
[0050] Add 8 g of modified montmorillonite dispersion C (filling ratio 5%) to the above polyamic acid solution, continue stirring for 2 hours, and obtain inorganic modified polyamic acid. Filter the prepared polyamic acid resin and perform defoaming treatment. Use a scraper coating device to coat the filtered polyamic acid resin, heat at 60°C for 1 hour, 120°C for 0.5 hours, and 180°C for 0.5 hours to obtain a polyimide gel film. Fix the obtained polyimide gel film on a cutting board so that the four sides are fixed, and then gradually perform high-temperature imidization in an oven at 200°C×5min, 350°C×3min, and 400°C×3min to obtain a polyimide film with a thickness of 50um.
[0051] It is particularly pointed out that: the aminosilane coupling agent is γ-mercaptopropyltrimethoxysilane (KH590), the dosage of the aminosilane coupling agent is 1-3%wt of the nano filler; the nanoparticles are titanium dioxide or zirconium dioxide or a mixture of titanium dioxide and zirconium dioxide, the addition amount of the inorganic nanoparticle filler accounts for 1-15% of the total weight of the solid content of the polyamic acid solution, and the particle size of the inorganic nanoparticle filler is 0.5-100nm;
[0052] Montmorillonite modification is achieved by mixing and dispersing sodium polyamic acid and montmorillonite. Since the binding strength between Na+ and Al and Mg is greater than that between Ca2+ and Al and Mg, Na+ replaces Ca2+ between bentonite layers to achieve the purpose of sodium modification, and the polyamic acid groups are grafted onto the montmorillonite surface.
[0053] Montmorillonite has a lamellar structure. By mixing the modified nanoparticle dispersion with the modified montmorillonite suspension, the inorganic nanoparticles are combined with the montmorillonite. Since the montmorillonite material is surface-grafted, the nanoparticle intercalation modified montmorillonite composite material has high compatibility and can be well dispersed in the polyimide resin.
[0054] The specific surface area of the montmorillonite powder is 240m2 / g, the sodium polyamic acid is homemade, the molecular weight Mn of the sodium polyamic acid is controlled between 2000-10000, and the amount of sodium polyamic acid added is 2-5% of the mass of the montmorillonite powder; the mass ratio of nanoparticles to montmorillonite is 1:1, and the filler particle size must be lower than 100nm, otherwise it will cause the haze of the transparent polyimide film to increase; the solid content of the polyamic acid solution is 10-20wt%, and the viscosity of the polyamic acid solution is 5000-30000cP.
[0055] The preparation of polyamic acid is the same as the conventional method, and is obtained by polymerization of diamine and dianhydride, wherein the diamine can be 4,4'-bis(4-aminophenoxy)diphenyl sulfone (pBAPS), 4,4'-bis(3-aminophenoxy)diphenyl sulfone (mBAPS), 1,3-bis(3-aminophenoxy)benzene (APB-N), 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane (HFBAPP), 4,4'-diaminodiphenyl sulfone (44DDS), 3,3'-diaminodiphenyl sulfone (33DDS), 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), bicyclo[2.2. 1] Heptanedimethylamine (NBDA), 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether (6FODA), 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP), 2,2-bis(4-aminophenyl)hexafluoropropane (Bis-A-AF), 4,4'-[1,4-phenylbis(oxy)]bis[3-(trifluoromethyl)aniline] (FAPB), 5(6)-amino-1-(4-aminophenyl)-1,3,3-trimethylindane (TMDA), 9,9-bis(4-aminophenyl)fluorene (BAFL), and meta-phenylenediamine (mPDA) must be composed of at least one of the above diamines.
[0056] The dianhydride may be 4,4-hexafluoroisopropylphthalic anhydride (6FDA), bisphenol A diether dianhydride (BPADA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3,4,4-diphenylsulfonetetracarboxylic anhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA), 1,2,3,4-cyclobutanetetracarboxylic anhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic anhydride (HPMDA), bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic anhydride (BTA), 2,3,3',4'-biphenyltetracarboxylic anhydride (α-BPDA), and must be composed of at least one of the above dianhydrides.
[0057] Example 2 (parts specifically mentioned in Example 1 will not be described again): A high-hardness transparent polyimide film, the preparation method of which is as follows:
[0058] Take 50g zirconium dioxide powder, the average particle size of which is 50nm, add 200g NMP polar solvent, add KH5901g, mix and disperse ultrasonically for 2h to obtain a uniform and stable modified titanium dioxide powder dispersion. The solid content of dispersion A is 25%; take 50g acid-treated montmorillonite powder, the specific surface area of which is 240m2 / g, add 2.5g sodium polyamic acid powder and 200g N,N-dimethylacetamide (DMAC), mix and disperse mechanically at high speed for 2h to obtain a uniform and stable modified montmorillonite dispersion. The solid content of dispersion B is 25%; mix dispersion A with dispersion B, continue ultrasonic dispersion for 4h to obtain zirconium dioxide intercalated modified montmorillonite dispersion C. Test the average particle size of dispersion C.
[0059] In a 500 ml glass separable flask equipped with a stirring device and a stirring blade, 115 g of a solvent N,N-dimethylacetamide (DMAC) and 16.012 g (0.0500 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) as an aromatic diamine compound having a fluorine group were added and stirred to dissolve TFMB in DMAC. Next, while stirring the inside of the separable flask, 22.3225 g (0.0502 mol) of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride (6FDA) as a tetracarboxylic dianhydride was added over a period of about 10 minutes under a nitrogen gas stream, and the temperature was adjusted to a temperature range of 20 to 40° C. in this state, and the stirring was continued for 6 hours to perform a polymerization reaction, thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.005, and the concentration of the polyamic acid solution was 25% by weight.
[0060] Add 8 g of modified montmorillonite dispersion C (filling ratio 5%) to the above polyamic acid solution, continue stirring for 2 hours, and obtain inorganic modified polyamic acid. Filter the prepared polyamic acid resin and perform defoaming treatment. Use a scraper coating device to coat the filtered polyamic acid resin, heat at 60°C for 1 hour, 120°C for 0.5 hours, and 180°C for 0.5 hours to obtain a polyimide gel film. Fix the obtained polyimide gel film on a cutting board so that the four sides are fixed, and then gradually perform high-temperature imidization in an oven at 200°C×5min, 350°C×3min, and 400°C×3min to obtain a polyimide film with a thickness of 50um.
[0061] Example 3 (parts specifically mentioned in Example 1 will not be described again): A high-hardness transparent polyimide film, the preparation method of which is as follows:
[0062] Take 25g zirconium dioxide powder and 25g titanium dioxide powder, the average particle size of the two powders is 50nm, add 200gNMP polar solvent, add KH5901g, mix and ultrasonically disperse for 2h to obtain a uniform and stable modified titanium dioxide powder dispersion. The solid content of dispersion A is 25%; take 50g acid-treated montmorillonite powder, the specific surface area of which is 240m2 / g, add 2.5g sodium polyamic acid powder and 200g N,N-dimethylacetamide (DMAC), mix and mechanically disperse at high speed for 2h to obtain a uniform and stable modified montmorillonite dispersion. The solid content of dispersion B is 25%; mix dispersion A with dispersion B, continue ultrasonic dispersion for 4h, and obtain zirconium dioxide intercalation modified montmorillonite dispersion C.
[0063] In a 500 ml glass separable flask equipped with a stirring device and a stirring blade, 115 g of a solvent N,N-dimethylacetamide (DMAC) and 16.012 g (0.0500 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) as an aromatic diamine compound having a fluorine group were added and stirred to dissolve TFMB in DMAC. Next, while stirring the inside of the separable flask, 22.3225 g (0.0502 mol) of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride (6FDA) as a tetracarboxylic dianhydride was added over a period of about 10 minutes under a nitrogen gas stream, and the temperature was adjusted to a temperature range of 20 to 40° C. in this state, and the stirring was continued for 6 hours to perform a polymerization reaction, thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.005, and the concentration of the polyamic acid solution was 25% by weight.
[0064] Add 16 g of modified montmorillonite dispersion C (filling ratio 10%) to the above polyamic acid solution, continue stirring for 2 hours, and obtain inorganic modified polyamic acid. Filter the prepared polyamic acid resin and perform defoaming treatment. Use a scraper coating device to coat the filtered polyamic acid resin, heat at 60°C for 1 hour, 120°C for 0.5 hours, and 180°C for 0.5 hours to obtain a polyimide gel film. Fix the obtained polyimide gel film on a cutting board so that the four sides are fixed, and then gradually perform high-temperature imidization in an oven at 200°C×5min, 350°C×3min, and 400°C×3min to obtain a polyimide film with a thickness of 50um.
[0065] Comparative Example 1: A high-hardness transparent polyimide film, the preparation method of which is as follows:
[0066] In a 500 ml glass separable flask equipped with a stirring device and a stirring blade, 115 g of a solvent N,N-dimethylacetamide (DMAC) and 16.012 g (0.0500 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) as an aromatic diamine compound having a fluorine group were added and stirred to dissolve TFMB in DMAC. Next, while stirring the inside of the separable flask, 22.3225 g (0.0502 mol) of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride (6FDA) as a tetracarboxylic dianhydride was added over a period of about 10 minutes under a nitrogen gas stream, and the temperature was adjusted to a temperature range of 20 to 40° C. in this state, and the stirring was continued for 6 hours to perform a polymerization reaction, thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.005, and the concentration of the polyamic acid solution was 25% by weight.
[0067] The prepared polyamic acid resin was filtered and defoamed. The filtered polyamic acid resin was coated by a scraper coating device, heated at 60°C for 1H, 120°C for 0.5H, and 180°C for 0.5H to obtain a polyimide gel film. The obtained polyimide gel film was fixed on a cutting board so that the four sides were fixed, and then gradually subjected to high-temperature imidization in an oven at 200°C×5min, 350°C×3min, and 400°C×3min to obtain a polyimide film with a thickness of 50um.
[0068] Comparative Example 2: A high-hardness transparent polyimide film, the preparation method of which is as follows:
[0069] Take 25g zirconium dioxide powder and 25g titanium dioxide powder, the average particle size of the two powders is 50nm, add 200gNMP polar solvent, add KH5901g, mix and ultrasonically disperse for 2h to obtain a uniform and stable modified titanium dioxide powder dispersion. The solid content of dispersion A is 25%; take 50g acid-treated montmorillonite powder, the specific surface area of which is 240m2 / g, add 2.5g sodium polyamic acid powder and 200g N,N-dimethylacetamide (DMAC), mix and mechanically disperse at high speed for 2h to obtain a uniform and stable modified montmorillonite dispersion. The solid content of dispersion B is 25%; mix dispersion A with dispersion B, continue ultrasonic dispersion for 4h, and obtain zirconium dioxide intercalation modified montmorillonite dispersion C.
[0070] In a 500 ml glass separable flask equipped with a stirring device and a stirring blade, 115 g of a solvent N,N-dimethylacetamide (DMAC) and 16.012 g (0.0500 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFMB) as an aromatic diamine compound having a fluorine group were added and stirred to dissolve TFMB in DMAC. Next, while stirring the inside of the separable flask, 22.3225 g (0.0502 mol) of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)diphthalic dianhydride (6FDA) as a tetracarboxylic dianhydride was added over a period of about 10 minutes under a nitrogen gas stream, and the temperature was adjusted to a temperature range of 20 to 40° C. in this state, and the stirring was continued for 6 hours to perform a polymerization reaction, thereby obtaining a viscous polyamic acid solution. The molar ratio of the tetracarboxylic dianhydride / aromatic diamine compound used was 1.005, and the concentration of the polyamic acid solution was 25% by weight.
[0071] Add 16 g of modified montmorillonite dispersion C (filling ratio 10%) to the above polyamic acid solution, continue stirring for 2 hours, and obtain inorganic modified polyamic acid. Filter the prepared polyamic acid resin and perform defoaming treatment. Use a scraper coating device to coat the filtered polyamic acid resin, heat at 60°C for 1 hour, 120°C for 0.5 hours, and 180°C for 0.5 hours to obtain a polyimide gel film. Fix the obtained polyimide gel film on a cutting board so that the four sides are fixed, and then gradually perform high-temperature imidization in an oven at 200°C×5min, 350°C×3min, and 400°C×3min to obtain a polyimide film with a thickness of 50um.
[0072] The performance comparison is shown in Table 1:
[0073]
[0074] It can be seen from Table 1 that the pencil hardness of Examples 1-3 is significantly higher than that of the comparative example. The present invention can prepare a transparent polyimide film with high hardness.
[0075] See also Figure 1-13As shown, as the preferred technical solution of this embodiment, the scraper coating device includes a workbench 1, a glass substrate 11, a work frame 2, a lifting mechanism 3, a cross bar 31, a detection mechanism 4, a scraper 5, a residual mechanism 6, a recovery mechanism 7, and a lifting and leveling mechanism 8. The workbench 1 is a fixed foundation, and a glass substrate 11 is arranged in the middle of the workbench 1; the work frame 2 is connected to the edge of the workbench 1 through an electric slide rail; the lifting mechanism 3 is installed on the cross bar 31 arranged between the work frames 2, and the lower end of the lifting mechanism 3 is connected to the detection mechanism 4, and the detection mechanism 4 is slidably arranged in the inner cavity opened by the scraper 5; the residual mechanism 6 is installed on the left side of the scraper 5, and the recovery mechanism 7 used in conjunction with the residual mechanism 6 is installed on the cross bar 31; the lifting and leveling mechanism 8 is installed on the right side of the lower end of the workbench 1.
[0076] In the above technical scheme, before the scraper is coated, the gap between the scraper 5 and the glass substrate 11 is detected, and the detection steps are as follows: the detection mechanism 4 and the scraper 5 are driven to descend synchronously by the lifting mechanism 3 until the scraper 5 contacts the lifting and leveling mechanism 8, and then the detection solution is injected into the inner cavity of the scraper 5, and then the scraper 5 in contact with it is driven to rise again by the lifting and leveling mechanism 8. During the rising process, when there is still a gap between the lower end surface of the scraper 5 and the lifting and leveling mechanism 8, it can be determined that the lower end surface of the scraper 5 is uneven. At this time, the scraper 5 is disassembled for further inspection. When the lower end surface of the scraper 5 is seamlessly fitted with the lifting and leveling mechanism 8, the detection solution will not leak out. As the scraper 5 further rises (the space of the inner cavity is compressed) and there is no detection solution, the scraper 5 is removed from the glass substrate 11. When the testing solution seeps out, the testing solution in the inner cavity is discharged multiple times through the residual mechanism 6 until it is completely recovered. When the scraper 5 and the cross bar 31 are reduced to the minimum gap, the lifting and leveling mechanism 8 and the scraper 5 stop rising, and the detection mechanism 4 further levels the flatness of the lower end surface of the scraper 5 (the position between the detection mechanism 4 and the scraper 5 is temporarily locked at this time). Then, the detection mechanism 4 and the scraper 5 are driven to descend synchronously by the lifting mechanism 3 until the gap between the scraper 5 and the glass substrate 11 is controlled to be 500um, and the filtered polyamic acid resin is poured onto the glass substrate 11. The working frame 2 is controlled to move to the left by the electric slide rail, and the scraper 5 with the gap adjusted is used for scraper coating, so as to obtain a polyimide gel film with the required thickness.
[0077] See also Figure 7-Figure 8As shown, the lifting mechanism 3 includes a rotating member 32, a threaded barrel 33, a lifting member 34, a sliding rod 35, an electric push rod 36, and a guide rod 37. The rotating member 32 is connected to the threaded barrel 33 by threaded cooperation, and the threaded barrel 33 is fixedly installed in the middle of the upper end of the cross bar 31; the upper end of the lifting member 34 is horizontally rotated and connected to the rotating member 32, and the lifting member 34 is slidably arranged in a sliding hole opened in the middle of the cross bar 31; the upper end of the sliding rod 35 is slidably arranged inside the lifting member 34, and an electric push rod 36 is connected between the lifting member 34 and the sliding rod 35; the lower end of the guide rod 37 is installed on one side of the scraper 5, and the guide rod 37 is slidably arranged on the cross bar 31.
[0078] In the actual adjustment process, the height is adjusted by rotating the rotating part 32 to perform spiral lifting, and the lifting part 34 follows the linear lifting to a suitable height. At this time, the height of the scraper 5 meets the requirements. Subsequently, the guide rod 37 and the scraper 5 are driven down by the electric push rod 36 until the lower end surface of the scraper 5 is in contact with the upper surface of the low glass layer 82.
[0079] See also Fig. 9 , Fig.10 , Fig.12 As shown, in order to detect whether the lower end surface of the scraper 5 and the glass layer 82 are in seamless contact, the present application detects this situation through a detection mechanism 4, and the specific structure is as follows: the detection mechanism 4 includes a connecting plate 41, a blocking block 42, a movable plate 43, a clamping member 44, and a top support member 45. The connecting plate 41 is connected to the lower end of the sliding rod 35, and the connecting plate 41 is slidably arranged in the inner cavity. The lower end of the connecting plate 41 is evenly installed with blocking blocks 42, and the lower end of the blocking block 42 is installed with a blocking head; the movable plate 43 is slidably sleeved on the blocking block 42, and the movable plate 43 and the connecting plate 41 are elastically connected; the clamping member 44 is horizontally slidably arranged in a built-in groove opened at the end of the connecting plate 41, and the clamping member 44 and the built-in groove are elastically connected, and the top support member 45 corresponding to the position of the clamping member 44 is horizontally slidably arranged in the movable groove opened on the side wall of the scraper 5.
[0080] See also Figure 5 , Fig.12 As shown, the front and rear ends of the working frame 2 are symmetrically equipped with fixed plates 21, and the inner end of the fixed plate 21 is equipped with a correction block 22, and the position of the correction block 22 and the top support member 45 corresponds to each other. When the scraper 5 is at the initial height (this state is before the electric push rod 36 drives the guide rod 37 and the scraper 5 descends for the first time), the correction block 22 squeezes the top support member 45 so that the top support member 45 is completely retracted into the movable groove. The fully retracted top support member 45 squeezes the clamping member 44 out of the movable groove. At this time, the clamping member 44 is not clamped with the movable groove, and the connecting plate 41 is in an unlocked sliding state in the inner cavity.
[0081] See also Fig. 9 , Fig.10 , Fig.12 As shown, a spray outlet is provided on the lower end face of the scraper 5, and the spray outlet is composed of a rectangular groove 51 and a spray hole 52 connected up and down. The rectangular groove corresponds to the position of the blocking block 42, and the spray hole 52 corresponds to the position of the blocking head. Adjacent rectangular grooves 51 are connected through a through hole 53 provided at the lower end of the scraper 5. A T-slot 421 is provided inside the blocking block 42. The opening of the through hole 53 provides a state of interconnection between adjacent rectangular grooves 51, thereby avoiding the situation that the detection solution cannot be discharged in time under the action of the upper pressure when the lower end face of the scraper 5 is seamlessly attached to the glass layer 82. The rectangular groove 51 provides a temporary space expansion effect. When the blocking block 42 is fully inserted into the rectangular groove 51, the T-slot 421, the rectangular groove 51 and the conveying chamber 54 provided inside the blocking block 42 are in a connected state, and the internal detection solution can be extracted and conveyed through the residual mechanism 6 later.
[0082] See also Figure 7 , Fig.10 As shown, the conveying cavity 54 opened on the left side of the scraper 5 is connected with the rectangular groove 51, and an input port 55 is opened on the right side of the inner cavity. The upper left side of the input port 55 is connected to the closure 56 through a pin shaft, and the closure 56 plays a role of opening and closing the input port 55. When the connecting plate 41 is in a high position in the inner cavity, the detection solution is transported to the input port 55 and the closure 56 is pushed open to be transported to the inner cavity. When the connecting plate 41 descends, the closure 56 is blocked by the side wall of the connecting plate 41, thereby isolating and closing the input port 55.
[0083] See also Fig. 9 , Fig.10 , Fig.13 As shown, the delivery chamber 54 includes an output chamber 531 , an expansion chamber 532 , and a Z-shaped chamber 533 , and the output chamber 531 , the expansion chamber 532 , and the Z-shaped chamber 533 arranged from top to bottom are connected to each other.
[0084] In the actual detection process, the electric push rod 36 drives the guide rod 37 and the scraper 5 to descend synchronously (the connecting plate 41 is located above the inner cavity, and the distance between the upper end face of the scraper 5 and the cross bar 31 is at the maximum value) until the lower end face of the scraper 5 is in contact with the upper surface of the low-position glass layer 82. At this time, the scraper 5 stops descending and the detection solution is injected into the inner cavity (the detection solution is located below the movable plate 43). After the injection is completed, the glass layer 82 is driven to rise by the lifting and leveling mechanism 8. The scraper 5 is in an ascending state relative to the connecting plate 41, so that the connecting plate 41, the blocking block 42, and the movable plate 43 push the detection solution in the inner cavity downward into the rectangular groove 51 and the ejection hole 52. If there is a gap between the lower end face of the scraper 5 and the glass layer 82 when they are in contact, the pressurized detection solution partially seeps out from this position, and it is determined that there is an uneven or notched position on the lower end face of the scraper 5. If the lower end face of the scraper 5 and the glass layer 82 are in seamless contact, the detection solution will not seep out from this position. Under the action of pressure, the detection solution to be discharged will enter the Z-shaped cavity 533 and the through hole 53 for temporary retention (the partition state between the expansion cavity 532 and the Z-shaped cavity 533). When no penetration occurs, the glass layer 82 is driven to rise to the highest position through the lifting and leveling mechanism 8. At this time, the upper end surface of the scraper 5 is attached to the lower side of the movable plate 43, the blocking block 42 enters the rectangular groove, and the blocking head is inserted into the ejection hole 52, thereby leveling the lower end surface of the scraper 5 (ejection hole 52). The hole 52 has been filled), and the clamping piece 44 is clamped in the movable groove so that the position of the connecting plate 41 and the inner cavity of the scraper 5 is temporarily locked (ensuring that the filling state of the lower end surface of the scraper 5 is maintained for a period of time), and then the remaining detection solution is extracted and transported through the residual mechanism 6 and the recovery mechanism 7, and then the guide rod 37 and the scraper 5 with the filled lower end surface are driven by the electric push rod 36 to synchronously descend until the gap between the scraper 5 and the glass substrate 11 is controlled at 500um, and then the scraper coating operation is carried out.
[0085] See also Fig. 9 , Fig.13As shown, the detection solution after the detection is recovered by the residual mechanism 6 and the recovery mechanism 7. The specific structure of the residual mechanism 6 is as follows: the residual mechanism 6 includes a trigger member 61, a partition member 62, a docking joint 63, a partition plate 64, a sealing plate 65, and a spring telescopic rod 66. The trigger member 61 is slidably arranged in the sliding groove provided in the scraper 5. The middle part of the trigger member 61 is elastically connected to the sliding groove. The lower end of the trigger member 61 is provided with a partition member 62 for controlling the flow of the Z-shaped cavity 533. The middle and upper parts of the partition member 62 are The middle part of the part is a hollow structure, and the docking joint 63 is fixedly installed at the upper end position of the outer wall of the scraper 5. The output chamber 531 is connected to the interior of the docking joint 63. The interior of the docking joint 63 is symmetrically installed with partition plates 64. The sealing plate 65 used in conjunction with the partition plate 64 is installed at the upper end of the spring telescopic rod 66. When the partition plate 64 is in contact with the sealing plate 65 at the highest position, the docking joint 63 is partitioned. The spring telescopic rod 66 is fixedly installed inside the docking joint 63, and the spring telescopic rod 66 always maintains a trend of driving the sealing plate 65 to rise.
[0086] See also Fig.13 As shown, the recovery mechanism 7 includes an insertion head 71, which is connected to the suction port of a pump body 72 installed on the cross bar 31. The output port of the pump body 72 is connected to a recovery frame 73 through a hose. The recovery frame 73 is fixed to the side end of the cross bar 31, and a protrusion 74 is installed inside the insertion head 71.
[0087] In the actual recycling process, after the lower end face of the scraper 5 is attached to the upper surface of the low glass layer 82, the detection solution is injected into the inner cavity. After the injection is completed, the glass layer 82 is driven to rise by the lifting and leveling mechanism 8, and the scraper 5 is in an ascending state relative to the connecting plate 41. In the early stage of the rise, the detection solution flows downward into the rectangular groove under the action of the upper pressure. When no infiltration occurs, the Z-shaped cavity 533 and the through hole 53 can also temporarily retain the delivered detection solution (the Z-shaped cavity 533 and the expansion cavity 532 are blocked by the partition 62, which ensures that the delivery space of the early detection solution is not large. When the connecting plate 41, the blocking block 42, and the movable plate 43 are pressed down, a certain retention space is given to the detection solution, and a certain downward pushing pressure is also given, thereby ensuring the completion of the seepage operation). As the scraper 5 continues to move upward, the glass layer 82 is driven to rise by the lifting and leveling mechanism 8, and the glass layer 82 is driven to rise. As the scraper 5 continues to rise, the internal space of the Z-shaped cavity 533 and the through hole 53 is difficult to ensure the subsequent retention of the detection solution. At this time, the trigger member 61 contacts the cross bar 31, and as the scraper 5 continues to rise, the trigger member 61 is subjected to pressure above and gradually drives the partition member 62 to descend relative to the scraper 5. The hollow structure of the partition member 62 is aligned with the Z-shaped cavity 533. At this time, the Z-shaped cavity 533 is connected to the expansion cavity 532, and the detection solution can flow into the expansion cavity 532. The lifting and leveling mechanism 8 drives the glass layer 82 to rise to the highest position. At this time, the upper end surface of the scraper 5 is attached to the bottom of the movable plate 43, the insertion head 71 is docked with the docking head 63, and the extension member 74 pushes the sealing plate 65 downward to separate it from the partition plate 64. At this time, the docking head 63 is in an open state, and the detection solution can be subsequently extracted and recovered into the recovery frame 73 by the pump body 72.
[0088] See also Figure 4 , Fig.11 As shown, the lifting and leveling mechanism 8 includes a lifting platform 81, a lifting component 811, a glass layer 82, a liquid storage frame 83, a docking port 84, and a delivery pump 85. The lifting platform 81 is connected to the lower end of the workbench 1 through the lifting component 811, and the upper end surface of the lifting platform 81 is paved with a glass layer 82. The liquid storage frame 83 is installed at the lower position of the workbench 1. The liquid storage frame 83 and the docking port 84 are connected to the delivery pump 85 through a connecting pipe. The docking port 84 is installed at the inner side wall of the through groove opened at the right end of the workbench 1, and the through groove is located directly above the lifting platform 81 at the initial position.
[0089] During the actual operation, the guide rod 37 and the scraper 5 are driven to descend synchronously by the electric push rod 36. After passing through the groove, the scraper 5 continues to descend until the lower end surface of the scraper 5 is in contact with the upper surface of the low glass layer 82. At this time, the docking port 84 is aligned with the input port 55. The detection solution in the liquid storage frame 83 is delivered to the docking port 84 by the delivery pump 85 and then injected into the inner cavity. After the injection is completed, the lifting platform 81 and the glass layer 82 are driven to rise by the lifting assembly 811 until the upper end surface of the glass layer 82 and the upper end surface of the glass substrate 11 are in the same horizontal plane.
[0090] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a high-hardness transparent polyimide film, characterized in that: The following steps are involved: Step 1: Take 50g of filler with an average particle size of 50nm, add 200g of NMP polar solvent, add 1g of KH590, mix and disperse by ultrasonic for 2h to obtain a uniform and stable modified dispersion, which is A dispersion and has a solid content of 25%; Step 2: Take 50g of acid-treated montmorillonite powder, the specific surface area of which is 240m2 / g, add 2.5g of sodium polyamic acid powder and 200g of N,N-dimethylacetamide, mix and disperse mechanically at high speed for 2h to obtain a uniform and stable modified montmorillonite dispersion, which is dispersion B and has a solid content of 25%; Step 3: Mix the dispersion A and the dispersion B, and continue ultrasonic dispersion for 4 hours to obtain a modified montmorillonite dispersion C; Step 4: Add 115 g of N,N-dimethylacetamide as a solvent and 16.012 g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl as an aromatic diamine compound having a fluorine group into a flask and stir. While stirring the inside of the flask, add 22.3225 g of 4,4'-(1,1,1,3,3,3-hexafluoropropane-2,2-diyl) diphthalic dianhydride as a tetracarboxylic dianhydride under a nitrogen flow for 10 minutes. In this state, adjust the temperature to 30° C. and continue stirring for 6 hours to perform a polymerization reaction to obtain a viscous polyamic acid solution; Step 5: Add 8-16 g of modified montmorillonite dispersion C to the polyamic acid solution in step S4, and continue stirring for 2 h to obtain an inorganic modified polyamic acid resin; Step 6: filtering the prepared polyamic acid resin, performing a defoaming treatment, and coating the filtered polyamic acid resin with a doctor blade coating device to obtain a polyimide gel film; Step 7: Fix the obtained polyimide gel film on a cutting board, fix its four sides, and then gradually perform high-temperature imidization in an oven to obtain a polyimide film with a thickness of 50 um.
2. The method for preparing a high-hardness transparent polyimide film according to claim 1, characterized in that: The blade coating device comprises: A workbench (1), wherein a glass substrate (11) is arranged in the middle of the workbench (1); A work frame (2) connected to the edge of the workbench (1) via an electric slide rail; A lifting mechanism (3) is mounted on a crossbar (31) disposed between the working frames (2), and the lower end of the lifting mechanism (3) is connected to a detection mechanism (4), and the detection mechanism (4) is slidably disposed in an inner cavity formed by the scraper (5); A residual amount mechanism (6) is installed on the left side of the scraper (5), and a recovery mechanism (7) used in conjunction with the residual amount mechanism (6) is installed on the crossbar (31); A lifting and leveling mechanism (8) is installed at the right side of the lower end of the workbench (1).
3. The method for preparing a high-hardness transparent polyimide film according to claim 2, characterized in that: The lifting mechanism (3) comprises: A rotating member (32) is connected to a threaded barrel (33) by means of threaded engagement, and the threaded barrel (33) is fixedly mounted at the middle of the upper end of the crossbar (31); A lifting member (34) whose upper end is connected to the rotating member (32) in a horizontal rotational manner, and the lifting member (34) is slidably arranged in a sliding hole provided in the middle of the crossbar (31); A sliding rod (35) whose upper end is slidably disposed inside the lifting member (34) and an electric push rod (36) is connected between the lifting member (34) and the sliding rod (35); The guide rod (37) has its lower end mounted on one side of the scraper (5), and the guide rod (37) is slidably mounted on the crossbar (31) up and down.
4. The method for preparing a high-hardness transparent polyimide film according to claim 2, characterized in that: The detection mechanism (4) comprises: A connecting plate (41) is connected to the lower end of the sliding rod (35), a blocking block (42) is evenly installed at the lower end of the connecting plate (41), and a blocking head is installed at the lower end of the blocking block (42); A movable plate (43) is slidably sleeved on the blocking block (42) up and down, and the movable plate (43) is elastically connected to the connecting plate (41); The clamping member (44) is horizontally slidably arranged in a built-in groove opened at the end of the connecting plate (41), and the clamping member (44) and the built-in groove are elastically connected. The supporting member (45) corresponding to the position of the clamping member (44) is horizontally slidably arranged in a movable groove opened on the side wall of the scraper (5).
5. The method for preparing a high-hardness transparent polyimide film according to claim 4, characterized in that: The front and rear ends of the working frame (2) are symmetrically mounted with fixing plates (21), the inner end of the fixing plate (21) is mounted with a correction block (22), and the positions of the correction block (22) and the supporting member (45) correspond to each other; The lower end surface of the scraper (5) is provided with a spray outlet, the spray outlet is composed of a rectangular groove (51) and a spray hole (52) connected up and down, adjacent rectangular grooves (51) are connected through a through hole (53) provided at the lower end of the scraper (5), and a T-shaped groove (421) is provided inside the blocking block (42); The conveying cavity (54) on the left side of the scraper (5) is connected to the rectangular groove (51), and an input port (55) is provided on the right side of the inner cavity. The upper left side of the input port (55) is connected to a closing member (56) via a pin shaft; The delivery chamber (54) comprises an output chamber (531), an expansion chamber (532), and a Z-shaped chamber (533), and the output chamber (531), the expansion chamber (532), and the Z-shaped chamber (533) arranged from top to bottom are connected to each other.
6. The method for preparing a high-hardness transparent polyimide film according to claim 5, characterized in that: The surplus mechanism (6) comprises: A trigger member (61) is slidably disposed in a sliding groove formed in the scraper (5) so as to slide up and down. The middle of the trigger member (61) is elastically connected to the sliding groove. A partition member (62) for controlling the flow of the Z-shaped cavity (533) is installed at the lower end of the trigger member (61). The middle of the upper middle portion of the partition member (62) is a hollow structure. A docking joint (63) is fixedly mounted at the upper end of the outer wall of the scraper (5); the output chamber (531) is connected to the interior of the docking joint (63); a partition plate (64) is symmetrically mounted inside the docking joint (63); a sealing plate (65) used in conjunction with the partition plate (64) is mounted on the upper end of a spring telescopic rod (66); and the spring telescopic rod (66) is fixedly mounted inside the docking joint (63); The recovery mechanism (7) comprises an insertion head (71), the insertion head (71) being connected to a suction port of a pump body (72) mounted on a cross bar (31), the discharge port of the pump body (72) being connected to a recovery frame (73) via a hose, the recovery frame (73) being fixed to a side end of the cross bar (31), and a protruding piece (74) being mounted inside the insertion head (71).
7. The method for preparing a high-hardness transparent polyimide film according to claim 2, characterized in that: The lifting and leveling mechanism (8) comprises: A lifting platform (81) is connected to the lower end of the workbench (1) via a lifting assembly (82), and a glass layer (82) is provided on the upper end surface of the lifting platform (81); A liquid storage frame (83) is installed below the workbench (1). The liquid storage frame (83) and a docking port (84) are connected to a delivery pump (85) via a connecting pipe. The docking port (84) is installed at the inner side wall of a through slot opened at the right end of the workbench (1). The through slot is located directly above the lifting platform (81) at the initial position.
8. The method for preparing a high-hardness transparent polyimide film according to claim 1, characterized in that: The filler is titanium dioxide.
9. The method for preparing a high-hardness transparent polyimide film according to claim 1, characterized in that: The filler is zirconium dioxide.
10. The method for preparing a high-hardness transparent polyimide film according to claim 1, characterized in that: The filler is a mixture of titanium dioxide and zirconium dioxide.